TO THE HISTORY OF THE BOSNIAN CONFLICT 1992-1995: POLITICAL COLLISION BETWEEN ACTIVE POWER AND OPPOSITION OF SERBIA CONCERNING TO RESOLVE THE SITUATION IN BOSNIA AND HERZEGOVINA - ЖУРЖА, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article examines the influence of external political factors on the domestic political life of the country. It states, that Bosnian conflict has become an great problem for active power of Serbia, that entered into open collision with opposition and caused political crisis. It researches positions of main political power of Serbia concerning ways of solution of the Bosnian conflict. It determines, that initial stages of aggravation of the situation in the Bosnia and Herzegovina, position of official Belgrade to resolve quite consistent efforts of t international community.